Ubicación del Eje de Rotación de una Articulación en Movimiento Mediante la Detección del Vector “r” - Martínez Lara, David; Ramírez García, Alfredo (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
A common problem found in biomechanical systems based on moving articulations is the real position of the rotation axis. The difficulty in encountering the rotation axis is due to it keeps changing its position at determined (aleatory or specific) time lapses, if the position and movement changes in every instant, so does the rotation axis. A useful tool that may solve this unknown is the cross product, because it considers the rotation of a vector “u” to a vector “v” (both constructed by the position changes of two points of reference) and the axis created on this movement. This principle could be applied for every instant of the move and could trace an approximation of where the axis is in each time instant.